Instrumentation numérique de la rédaction incrémentale : leçons tirées de la mise à l’épreuve du carnet numérique de l’élève chercheur - Cisel, Matthieu; Barbier, Charlotte (Canadian Journal of Education/Revue canadienne de l’éducation, 2021)
We studied how the introduction of the CNEC, a learning environment whose function is to foster iterative writing, affected the interactions between pupils and teachers in a sample of elementary and middle schools. Based on class observations and focus groups and through the lens of activity theory, we study the difficulties associated with the implementation of iterative writing, before and after the introduction of the CNEC. Our results corroborate the hypothesis that digital artifacts can improve the regulation of class activity in the context of inquiry-learning, compared to their paper equivalents. Parallelly, our results suggested that the perception students had of their own mistakes seems to change in a context of iterative writing, since the remarks of the teacher on such mistakes are less considered as a punishment. Observations also suggested that new contradictions could arise of the will of teachers to use both paper-based and digital artifacts to perform iterative writing, and due to the increased time the formulation of feedbacks requires. Keywords: iterative writing, evaluation, virtual learning environment